The Effect of Social Responsible Human Resource Management, Work Engagement Towads Employee Innovation Performance, with The Mediating of Person Organization-Fit In Companies - Prawira Kautsar, Marza; Puspitaloka Mahadewi, Erlina (Publisher Cv. Inara, 2026)
Human resource management oriented towards social responsibility increases competitiveness among companies in the civil engineering field, and attention to employee innovation performance is increasing. The purpose of this study is to examine the effect of human resource management on employee innovation performance, as well as the effect of human resource management on individual-organization fit, and human resource management on work engagement. It also examines the mediating effect of individual-organization fit. It also aims to provide a comprehensive understanding of how human resource management can improve employee innovation performance. Data was obtained through a g-form and using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method with the help of the SmartPLS 4.0 application, with a total of 181 private employees from civil engineering consulting companies in Greater Jakarta as respondents. The results of this study indicate that Socially Responsible Human Resources, Individual and Organizational Fit, and Work Engagement have a significant impact on Employee Innovation Performance. The mediating role of Individual and Organizational Fit on Employee Innovation Performance also has a significant impact. Recommendations include expanding the respondent area and focusing more on civil engineering consultant employees in Indonesia, as well as paying attention to sampling methods that are more representative. This study has managerial implications, namely encouraging employees to improve employee innovation performance in companies.